Antisemitism in football: international perspectives - Poulton, Emma (Critical research in football, 2025)
"This book investigates the nature and prevalence of expressions of antisemitism within the context of football in Europe and beyond, as well as attempts to challenge and combat this problematic phenomenon. Drawing on empirical research, the book presents a series of case studies of countries in which both football and antisemitism have been prominent, including England, Italy, Germany, Holland, Poland, Argentina and Hungary. Each chapter explains the historical context of why antisemitism prevails in their country and their country's football culture; considers those football clubs with a 'Jewish' heritage and identity (which tend to be the catalyst for antisemitic abuse); and critically examines the measures being taken in that country to tackle antisemitism in football by organisations including governing bodies, campaign groups, supporter groups and football clubs themselves. No other book has looked as deeply into this highly topical issue which continues to blight contemporary football. Antisemitism in Football is important reading for anybody with an interest in football, fan cultures, the sociology of sport, Jewish studies, antisemitism and other forms of racism and discrimination in society"--